2022
DOI: 10.3201/eid2802.210454
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsiosis Caused by Rickettsia parkeri, Mexico

Abstract: We report a human case of rickettsiosis caused by Rickettsia parkeri strain Atlantic Rainforest in Mexico in an adult woman from a small town in the north of Yucatan, Mexico. We confirmed diagnosis using conventional PCR and sequence analysis. Health providers should be aware of clinical manifestations of rickettsioses in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This study presents the unusual presence of R. parkeri in synanthropic rodents ( M. musculus ) and domiciled dogs from a rural community in southeastern Mexico. These findings involve, for the first time M. musculus as accidental hosts in the epidemiological cycle of this Rickettsia species endemic to the study region (Peniche‐Lara & Lara‐Perera, 2022; Torres‐Castro, Sánchez‐Montes, et al, 2022), and the case of the dogs, they reinforce their participation in the said epidemiological cycle (Sánchez‐Montes et al, 2021) after the identification of this Rickettsia species in a domiciliated dog from the study region by Ojeda‐Chi et al (2019).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This study presents the unusual presence of R. parkeri in synanthropic rodents ( M. musculus ) and domiciled dogs from a rural community in southeastern Mexico. These findings involve, for the first time M. musculus as accidental hosts in the epidemiological cycle of this Rickettsia species endemic to the study region (Peniche‐Lara & Lara‐Perera, 2022; Torres‐Castro, Sánchez‐Montes, et al, 2022), and the case of the dogs, they reinforce their participation in the said epidemiological cycle (Sánchez‐Montes et al, 2021) after the identification of this Rickettsia species in a domiciliated dog from the study region by Ojeda‐Chi et al (2019).…”
Section: Discussionmentioning
confidence: 84%
“…However, these ectoparasites have not been involved in the zoonotic transmission of R. parkeri . Recently, Peniche‐Lara and Lara‐Perera (2022) and Torres‐Castro, Sánchez‐Montes, et al (2022) reported the first cases of R. parkeri in symptomatic and asymptomatic inhabitants of Yucatán (southeastern Mexico). These records are relevant for public health because they show the circulation of this Rickettsia species among the inhabitants of Mexico (Sánchez‐Montes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Across México, rickettsiae pathogens have been described in vectors and hosts in northern Baja California, Sonora, Chihuahua [19], Campeche [20,21], Yucatán [22], Tabasco [23], Veracruz [21,24], Tamaulipas [24][25][26], and Coahuila [4,12,27]. Ongoing outbreaks of RMSF since 2008, with high fatality rates, in northwestern regions of México have been much of the focused surveillance, with human disease also reported from adjacent indigenous communities of Arizona [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Across Mexico, rickettsiae pathogens have been described in vectors and hosts in Northern Baja California, Sonora, Chihuahua [20], Campeche [21,22], Yucatan [23], Tabasco [24], Veracruz [22,25], Tamaulipas [25][26][27], and Coahuila [4,12,28]. Ongoing outbreaks of RMSF since 2008, with high fatality rates, in Northwestern regions of Mexico have been much of the focused surveillance, with human disease also reported from adjacent indigenous communities of Arizona [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%